Environmental impact of Norwegian food and beverages: compilation of a life cycle assessment food database - Monica Hauger Carlsen; Marie M. Bjøntegaard; Bob van Oort; Sepideh Jafarzadeh; Shraddha Mehta; Ellen C. Wright; Lene Frost Andersen (Food & Nutrition Research, 2025)
Background: Food production contributes to greenhouse gas emissions and pollution. Climate and environmental impacts from food production vary across geographical areas. To estimate these impacts of food and diets, country-specific data are needed. Objective: This project aimed to compile an environmental impact food database, including the impact categories (ICs) global warming potential, soil acidification, freshwater and saltwater eutrophication, water use and land use, representative of the Norwegian diet. Design: The compilation was based on literature searches for original life cycle assessment (LCA) studies on foods, including domestic and imported foods, which constitute the habitual diet in Norway. Food items of importance in the average Norwegian diet were identified based on the national dietary survey Norkost 3. The study’s generic system boundaries included impacts from farm to fork: production, processing, packaging, transportation, storage and food preparation at home. Conversion factors for edible portions were applied when relevant. When LCA data of a certain food were missing, data from foods with similar cultivation conditions and nutritional composition were used as proxies. Data from other LCA food databases were also used if original LCA studies were not identified, or the LCA studies found were evaluated as being of poor quality. Results: The compiled database is tailored specifically for and covers main animal- and plant-based foods in the Norwegian diet. Discussion: Limitations of the compilation project include the fact that most LCA studies identified in the present project covered ICs up to the farm gate and used varying methodology. Also, proxy values were used when data for specific food items were missing. These methodological issues introduce variability and complicate direct comparisons. The strength of the present study is the thorough work in compiling and filling data gaps for the IC values of foods in the Norwegian diet. Conclusions: The Norwegian LCA food database enables simultaneous estimation of food and nutrient intakes and estimation of climate and environmental impacts of Norwegian diets.